ANALISIS POTENSI WISATA ALAM DENGAN ADO-ODTWA: STUDI KASUS DESA KEMPO - Roseven Rudiyanto; Septian Hutagalung (JURNAL KEPARIWISATAAN, 2022)
The West Manggarai Regency Government has established 94 tourist villages in line with tourism development. One of the tourist villages in West Manggarai Regency is Kempo Village. The natural tourism potential of this village is Golo Cucu Hill, Liang Ndre Kalelawar Cave, and rice fields. However, there has been no study on the potential for natural tourism in Kempo Village. Therefore, this study aimed to analyze the potential for natural tourism in Kempo Village. This research approach was qualitative, with data collection techniques through focused group discussions and observation. Data analysis used the Guidelines for the Analysis of Working Areas for Natural Tourism Objects and Attractions (ADO-ODTWA). The results were seven aspects that have high feasibility categories, namely 1) tourist attraction, 2) conditions around the area, 3) management and services, 4) facilities and infrastructure, 5) availability of clean water, 6) security and 7) marketing. The aspect with a moderate eligibility category was accessibility, while the accommodation aspect had a low eligibility category. Thus, it can be concluded that the natural tourism potential in Kempo Village was highly feasible. However, there was a need for improvement in accommodation and accessibility aspects. Recommendations for the accommodation aspect were hospitality training for Pokdarwis members and the determination of community houses as homestays while improving the accessibility aspect could be done by making information boards and road signs to make it easier for tourists to visit.